Recent progress of second near-infrared (NIR-II) fluorescence microscopy in bioimaging - Wang, Tian; Chen, Yingying; Wang, Bo; Wu, Mingfu (Frontiers in Physiology, 2023)
Visualizing biological tissues in vivo at a cellular or subcellular resolution to explore molecular signaling and cell behaviors is a crucial direction for research into biological processes. In vivo imaging can provide quantitative and dynamic visualization/mapping in biology and immunology. New microscopy techniques combined with near-infrared region fluorophores provide additional avenues for further progress in vivo bioimaging. Based on the development of chemical materials and physical optoelectronics, new NIR-II microscopy techniques are emerging, such as confocal and multiphoton microscopy, light-sheet fluorescence microscopy (LSFM), and wide-field microscopy. In this review, we introduce the characteristics of in vivo imaging using NIR-II fluorescence microscopy. We also cover the recent advances in NIR-II fluorescence microscopy techniques in bioimaging and the potential for overcoming current challenges.